2018
DOI: 10.1080/24750573.2018.1426159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on therapeutic response in depression treatment

Abstract: OBJECTIVES:The aim of this study is to investigate the effect of exercise on therapeutic response in depression treatment. METHODS: Thirty-three patients admitted to the Psychiatry Department of Firat University Hospital and diagnosed with major depressive disorder according to DSM-IV criteria and met the study criteria were included in the study. The patients in Group 1 were treated with antidepressant medication and were asked for brisk walking for at least 30 minutes a day, at least 4 days a week, for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
13
0
3
Order By: Relevance
“…In the way from unborn 57.14% were having high level of self esteem and half of the subjects from rural 50% were having low level of self esteem. However, there was a statistically more decrease in the average-scaled scores in the Group treated with antidepressant and exercise than the Group treated with only antidepressant [14].…”
Section: Discussionmentioning
confidence: 75%
“…In the way from unborn 57.14% were having high level of self esteem and half of the subjects from rural 50% were having low level of self esteem. However, there was a statistically more decrease in the average-scaled scores in the Group treated with antidepressant and exercise than the Group treated with only antidepressant [14].…”
Section: Discussionmentioning
confidence: 75%
“…Exercise is found to be an effective way to decrease depression, anxiety and stress level with no side effect comparing with drug consumption [37]. Exercise regularly can improve physical health, life satisfaction, and psychological well-being.…”
Section: Subgroupmentioning
confidence: 99%
“…In another study showed that exercise with 30 minutes duration a day, four times a week, has the same effect as taking antidepressant drugs in reducing depression and anxiety level. That is why exercise has a positive effect on the therapeutic response in the treatment of depression [37].…”
Section: Subgroupmentioning
confidence: 99%
“…Physical activity (PA) is suggested to have a protective effect against depression and a positive effect on the treatment of depression in non-clinical and clinical populations, regardless of sex and age [9,10]. As non-pharmacology therapy, PA does not show drug side effects such as weight gain, insomnia, dry mouth, or withdrawal symptoms [11]. On the contrary, besides the positive benefits on depression, it is also associated with positive public health gains such as physical performance and cardiovascular improvements [11].…”
Section: Introductionmentioning
confidence: 99%
“…As non-pharmacology therapy, PA does not show drug side effects such as weight gain, insomnia, dry mouth, or withdrawal symptoms [11]. On the contrary, besides the positive benefits on depression, it is also associated with positive public health gains such as physical performance and cardiovascular improvements [11].…”
Section: Introductionmentioning
confidence: 99%